Contexts of reproduction: Gender dynamics and unintended birth in sub‐Saharan Africa. Issue 2 (15th October 2021) - Bras, Hilde; Smits, Jeroen
Abstract: Objective: This study examines how women's chances of having an unintended birth is related to gender inequalities in education, employment, intra‐household decision‐making, and norms at individual, household, and community levels in sub‐Saharan Africa (SSA). Background: Women in SSA have the highest rates of unintended births in the world, often with severe implications for the health and well‐being of families. A comprehensive understanding of how gender dynamics are associated with their chances of unintended birth is however lacking. Method: Multilevel binomial logistic regression models of unintended birth were estimated with harmonized data from 123 Demographic and Health Surveys including 534, 533 married women living in 43, 136 communities within 39 SSA countries over the period 1992–2019. Results: The odds of unintended birth are higher among higher‐educated women, women with a small age difference with their husband, and women living in communities with more higher‐educated women, and better (reproductive) health facilities. These women are more willing to acknowledge a birth as unintended. In communities where women are relatively more educated than their husband and in households where husbands and wives are equal in terms of education, higher occupational status, and fertility preferences, odds of unintended birth are lower. Conclusion: Unintended birth is a complex reproductive experience related to local gender systems, women's relative position in intra‐household power relations, and their willingness to acknowledge a birth as unintended. Implications: Improving gender equality at household level may result in women's improved reproductive health. However, outcomes are also strongly shaped by the local gender system.